Human Cytomegalovirus pUL93 Links Nucleocapsid Maturation and Nuclear Egress - DeRussy, Bernadette M. (J Virol, 2016)
Human cytomegalovirus (HCMV) pUL93 and pUL77 are both essential for virus growth, but their functions in the virus life cycle remain mostly unresolved. Homologs of pUL93 and pUL77 in herpes simplex virus 1 (HSV-1) and pseudorabies virus (PRV) are known to interact to form a complex at capsid vertices known as the capsid vertex-specific component (CVSC), which likely stabilizes nucleocapsids during virus maturation and also aids in nuclear egress. In herpesviruses, nucleocapsids assemble and partially mature in nuclear replication compartments and then travel to the inner nuclear membrane (INM) for nuclear egress. The factors governing the recruitment of nucleocapsids to the INM are not known. Kinetic analysis of pUL93 demonstrates that this protein is expressed late during infection and localizes primarily to the nucleus of infected cells. pUL93 associates with both virions and capsids and interacts with the components of the nuclear egress complex (NEC), namely, pUL50, pUL53, and pUL97, during infection. Also, multiple regions in pUL93 can independently interact with pUL77, which has been shown to help retain viral DNA during capsid assembly. These studies, combined with our earlier report of an essential role of pUL93 in viral DNA packaging, indicate that pUL93 serves as an important link between nucleocapsid maturation and nuclear egress. IMPORTANCE HCMV causes life-threatening disease and disability in immunocompromised patients and congenitally infected newborns. In this study, we investigated the functions of HCMV essential tegument protein pUL93 and determined that it interacts with the components of the nuclear egress complex, namely, pUL50, pUL53, and pUL97. We also found that pUL93 specifically interacts with pUL77, which helps retain viral DNA during capsid assembly. Together, our data point toward an important role of pUL93 in linking virus maturation to nuclear egress. In addition to expanding our knowledge of the process of HCMV maturation, information from these studies will also be utilized to develop new antiviral therapies.